ChemInform Abstract: Asymmetric Total Synthesis of (‐)‐trans‐Blechnic Acid via Rhodium(II)‐Catalyzed C—H Insertion and Palladium(II)‐Catalyzed C—H Olefination Reactions. Issue 28 (15th July 2014) - Ito, Motoki; Namie, Ryosuke; Krishnamurthi, Janagiraman; Miyamae, Hitomi; Takeda, Koji; Nambu, Hisanori; Hashimoto, Shunichi
Abstract (‐)‐trans‐blechnic acid (I) has an uncommon 2, 3‐cis‐stereochemistry and belongs to the dihydrobenzofuran neolignans, which exhibit several biological activities.